PULSE METHOD FOR DETERMINATION OF TIME PARAMETERS THERMAL FIRE DETECTOR: Array - Kozak, Ya. (Municipal economy of cities. Series: «Economy science», 2021)
For thermal fire detectors with a thermoresistive sensitive element, the method of determining its time parameters is justified. The time parameters of operation and the time constant of the thermal fire detector are considered as time parameters. The method is based on the use of the Joule-Lenz effect, for the implementation of which single pulses of electric current are passed through the thermoresistive sensitive element of the fire detector. Pulses having the shape of a quarter sinusoid or a quarter cosinusoid are used as such test signals. Using the Laplace integral transformation, analytical expressions are obtained, which represent the formalization of the reaction of the thermoresistive sensitive element of the fire detector to the corresponding test signals. These analytical expressions are used to obtain the functional dependences of the fire detector time constants on the pulse duration of the electric current and the auxiliary parameter. The auxiliary parameter is the ratio of the values ​​of the output signal of the thermal fire detector at two fixed points in time. This choice of auxiliary parameter allows to ensure invariance with respect to the transfer coefficient of the thermal fire detector with a thermoresistive sensing element. The fixed moments of time are chosen to be equal to half and three quarters of the duration of the pulses of electric current flowing through the thermoresistive sensitive element of the fire detector. The time of operation of the thermal fire detector is determined in the form of two additive components, one of which is a time constant of the fire detector, and the other is determined by the values ​​of normalized parameters in accordance with existing regulations. A sequence of procedures is given, which together represent a method of determining the time parameters of thermal fire detectors of this type.